2002
DOI: 10.1002/1521-3757(20020802)114:15<2903::aid-ange2903>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

[Ir4(CO)12]-Catalyzed Coupling Reaction of Imidazoles with Aldehydes in the Presence of a Hydrosilane to Give 2-Substituted Imidazoles

Abstract: Eine deutliche Ausbeutesteigerung bewirkt die Zugabe von Acetylendicarbonsäuredimethylester (DMAD) bei der Reaktion von 1‐Methylimidazol 1 mit Aldehyden 2 und Diethylmethylsilan in Gegenwart von [Ir4(CO)12] als Katalysator, die zu 2‐(1‐Diethylmethylsiloxyalkyl)imidazolen 3 führt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…To enable transition metal-catalyzed C–H bond additions to aldehydes, several strategies have been developed to overcome the inherent reversibility of this transformation. In seminal reports, the reversibly formed Ir-catalyzed alcohol addition products were captured as silyl ethers, 6 and this approach has now been extended to Mn, and Re. Trapping of alcohol addition products via irreversible in situ oxidation to the corresponding ketone has also been achieved, and significant progress has been accomplished for Pd and Rh catalysis.…”
Section: Aldehydesmentioning
confidence: 99%
See 2 more Smart Citations
“…To enable transition metal-catalyzed C–H bond additions to aldehydes, several strategies have been developed to overcome the inherent reversibility of this transformation. In seminal reports, the reversibly formed Ir-catalyzed alcohol addition products were captured as silyl ethers, 6 and this approach has now been extended to Mn, and Re. Trapping of alcohol addition products via irreversible in situ oxidation to the corresponding ketone has also been achieved, and significant progress has been accomplished for Pd and Rh catalysis.…”
Section: Aldehydesmentioning
confidence: 99%
“…6 The authors demonstrated that [Ir 4 (CO) 12 ] catalyzes the coupling of N -methylimidazole, 13 , and aldehydes in the presence of diethylmethylsilane to provide silyl protected alcohols 14 . Interestingly, dimethyl acetylenedicarboxylate (DMAD) as an additive significantly improved the reaction yield, which the authors proposed acts either as a hydrogen acceptor or a ligand.…”
Section: Aldehydesmentioning
confidence: 99%
See 1 more Smart Citation
“…8 This transformation provides a convenient synthetic route for chiral 3-substituted 3-hydroxy-2-oxindole derivatives with asymmetric induction. While some pioneering works have been reported, 9 only limited mechanistic information is available for aryl sp 2 C−H bond addition to carbonyl groups. Herein, we report the results of mechanistic studies of our newly developed intramolecular enantioselective hydroarylation reaction.…”
Section: ■ Introductionmentioning
confidence: 67%
“…In recent years, chemists have been struggling in this field and have made significant contributions 2. The beautiful example of C–H addition to aldehydes with the assistance of a silane was reported by Murai and co‐workers 3. Later on, the silane‐assisted strategy was further extended by Takai4 and our group5 in different systems.…”
Section: Introductionmentioning
confidence: 93%